THE ROLE OF SOCIAL IDENTITY IN SHAPING THE DISCOURSE OF “HOMELAND” IN PRINT MEDIA - Parpieva Shakhnoza Muratovna (International Journal of Literature and Language Studies, 2026)
This article investigates the relationship between social identity and the discursive construction of the concept «homeland» in print media. Drawing on Critical Discourse Analysis and Social Identity Theory, it examines how national, ethnic, political, and diasporic identities shape the linguistic representation of «homeland» in newspaper texts. The analysis reveals that the concept functions not as a neutral geographical term but as a dynamic ideological and emotional site through which social groups negotiate belonging, loyalty, and collective memory. Newspaper discourse both reflects and reinforces these identity-driven constructions through specific lexical, metaphorical, and evaluative strategies.